Intergroup conspiracy theories and covid vaccinations - Haiyan Wang; David Garcia de Nascimento; Jan-Willem van Prooijen (OSF Registries, 2021)
In a previous study we found that American participants were more likely to take a Covid-vaccine developed by American scientists than by Chinese scientists; moreover this effect was mediated by conspiracy beliefs. In this study we run a (slightly adapted) Chinese version of this study in a Chinese sample. The main prediction is that Chinese participants will be more likely to take a Covid-vaccine developed by Chinese scientists than by American scientists. Moreover, we expect this effect to be mediated by conspiracy beliefs.
Keywords: Social and Behavioral Sciences